Fishery Supporting Industry Planning for Karimunjawa Jepara Sea Far - Ratna Purwaningsih (khon kaen, usim, thamkang, umy, 2016)
Mari culture is an alternative solutions for Overfishing on capture fisheries. Mari culture on Karimunjawa Jepara district has been developing marine sea farming for commodity of seaweed, grouper fish and shellfish. The problems encountered recently is lack off supporting Industry to supply fish seed, feed fish and marine sea farming equipment and tools. Also, the infrastructure for fish handling, processing and marketing still inadequate. The development of marine sea farming industry requires government policy to encourage the emergence of supporting industries. As a huge investment needed, supporting industries can only be presented if the potential development of the sea farming industry is shown to have a high economic value. It is necessary to present an industry planning studies on marine sea farming. This paper aims to discuss (1) the type of supporting industry necessary, (2) the Interlinkage model between industry, and (3) estimate the number and size of industrial capacity based on available marine resources (land and water conditions). The research method was deep interviews, focus group discussions and a literature review. Result of the discussion would be useful to develop marine sea farming of Karimunjawa to become an industrial cluster which connected with the surrounding areas as supporting industries and market areas.